2008
DOI: 10.1159/000163443
|View full text |Cite
|
Sign up to set email alerts
|

Mortality from Occupational Exposure to Relatively Pure Chrysotile: A 39-Year Study

Abstract: Background: Asbestos exposure is related to serious adverse health effects. However, there is disagreement about the relationship between chrysotile exposure and mesothelioma or lung cancer. Objectives: Our aim was to investigate the mortality rate among workers exposed to relatively pure chrysotile in an asbestos cement factory. Patients and Methods: In an asbestos cement plant opened in 1968, we prospectively studied all 317 workers. A quantity of 2,000 tons of chrysotile, with minimal amphibole contaminatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 34 publications
0
19
0
6
Order By: Relevance
“…In Greece, Sichletidis et al (2009) considering a cohort of workers exposed to chrysotile found that the mortality for "all causes" was lower than that of the general population. Forastiere et al (1989) compared the mortality of a cohort of workers compensated for silicosis, and deceased in the period 1969-1984, with Latium population as in the present paper.…”
Section: Discussionmentioning
confidence: 97%
“…In Greece, Sichletidis et al (2009) considering a cohort of workers exposed to chrysotile found that the mortality for "all causes" was lower than that of the general population. Forastiere et al (1989) compared the mortality of a cohort of workers compensated for silicosis, and deceased in the period 1969-1984, with Latium population as in the present paper.…”
Section: Discussionmentioning
confidence: 97%
“…The amphibole and amosite are reported to carry the greater risk of causing other asbestos-related diseases such as pleural plaque, mesothelioma and lung cancer. Exposed workers who have developed asbestosis are at risk of fatal complications (Wagner, 1997;Sichletidis et al, 2009;Mossman et al, 1990). In patients with asbestosis, the chest radiograph usually shows small bilateral parenchymal opacities with a multinodular or reticular pattern that may be associated with pleural abnormalities.…”
Section: Asbestosis and Other Asbestos-related Diseases (Ards) 121 mentioning
confidence: 99%
“…Torbica and Krstev (2006) suggested that asbestos-related diseases in dentists might be linked to exposure to inorganic dust in the manufacturing of cobalt-chromiummolybdenum-based dental protheses. With the use of white asbestos-made lining material for casting rings in dentistry, dental technicians and dentists are potentially exposed to asbestos; and some cases of pleural plaques and malignant mesothelioma have been reported in a number of dentists after a relatively long period of work (35 to 45 years) (Choel et al, 2001;Reid et al, 1991;Sichletidis et at, 2009;Radi et al, 2002). Similarly, pneumoconiosis may occur in mechanics.…”
Section: Asbestosis and Other Asbestos-related Diseases (Ards) 121 mentioning
confidence: 99%
“…Достоверно известно, что высокие уровни экспозиции приводят к возникновению заболеваний раком лег-ких, но снова в исследованиях часто нет дифференциации по влиянию различных видов асбеста. Вопрос относительно того, вызывают ли низкие экспозиции риск развития рака легких, поскольку они ниже ку-мулятивного воздействия, находится в стадии изучения [10,13,[17][18][19][20][21][22][23][24][25][26][27][28].…”
unclassified
“…Во многих исследованиях [10,11,[17][18][19][20][21][22][23][24][25][26][27][28][29][30]] было показано, что хри-зотил не обладает теми же активными биологическими свойствами и онкоопасностью, что и амфиболы, и выводится из легких быстрее, чем амфиболовые волокна. В настоящее время получает распространение большое количество аналогов хризотил-асбеста, различных по своим химическим и физико-механическим свойствам: стеклянные, базальтовые, керамические, по-лимерные и др.…”
unclassified